2018
DOI: 10.1038/s41391-018-0081-6
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens and prostate cancer

Abstract: Estrogens represent a under-recognized contributor in CaP development and progression. Further research in this topic may provide opportunities for identification of environmental influencers as well as providing novel therapeutic targets in the treatment of CaP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 88 publications
2
53
1
1
Order By: Relevance
“…In conclusion, our results showed that exposure to chlordecone, an environmental EDCs with estrogenic properties, at the time of PCa diagnosis is significantly associated with a risk of BCR after prostatectomy. Increasing evidence suggests that estrogens are critical players in human PCa . Our findings add support to the hypothesis that human exposure to environmental estrogens may influence PCa progression.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In conclusion, our results showed that exposure to chlordecone, an environmental EDCs with estrogenic properties, at the time of PCa diagnosis is significantly associated with a risk of BCR after prostatectomy. Increasing evidence suggests that estrogens are critical players in human PCa . Our findings add support to the hypothesis that human exposure to environmental estrogens may influence PCa progression.…”
Section: Discussionsupporting
confidence: 84%
“…Increasing evidence suggests that estrogens are critical players in human PCa. 49,50 Our findings add support to the hypothesis that human exposure to environmental estrogens may influence PCa progression.…”
Section: Discussionsupporting
confidence: 79%
“…The function of ESR1 in NEPC has not yet been investigated, while its role on prostate tissue is ascertained. For this reason, there is an increasing interest in the use of SERMs (selective estrogen receptor modulators) as a potential singular or adjunctive agents for the treatment of PCa [37], with many ongoing clinical trials. Raloxifene, a mixed estrogen agonist/antagonist, has demonstrated some favorable results, particularly in androgen-independent CRPC [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Also, PCa ranks the fth leading cause of cancer death worldwide (2).With the development of economy and society, China is experiencing a transition stage from a developing country into a developed country, named as "westernized lifestyle-related cancer", so we can effortlessly draw the conclusion that there is an ascendant tendency in the incidence rates of PCa (3). Many conventional high-risk factors have been concerned with the period of tumorigenesis, invasion and metastasis of PCa, including genetic, environmental and life-style factors (4,5).…”
Section: Introductionmentioning
confidence: 99%